Athletes` perception of the causes of injury in gymnastics - Kolar, E.; Pavletic, M. S.; Smrdu, M.; Atikovic, A. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Gymnastics requires a high level of flexibility, conditioning and complete body recruitment that is infrequently matched by other sports. Artistic gymnastics has a relatively high incidence of injuries, which are generally of minor or medium severity. With all its complexity, it poses a unique diagnostic and treatment challenge to medical practitioners. The present study examined athletes' perception of the causes of injury and of the possible ways to reduce their incidence.